Positive Effects of Prosocial Cartoon Viewing on Aggression Among Children: The Potential Mediating Role of Aggressive Motivation - Zhang, Qian (Frontiers in Psychology, 2021)
Prosocial cartoon is characterized by helping others solve difficulties, including helping, donating, sharing, comforting, and cooperating. The current study examined whether viewing a prosocial cartoon decreases aggression immediately upon exposure and the potential mediating role of aggressive motivation. Participants involve 168 children (Mage = 5.87 years, SD = 0.41) nominated by teachers as aggressive from three Chinese kindergartens. Children in the treatment group watched a prosocial cartoon (American cartoon “Handy Manny”), while children in the control group watched a nonprosocial cartoon (Chinese cartoon “Fruity Robo”). Afterward, the Hot Sauce Task (HST) was employed to assess aggressive behavior, and Aggressive Motivation Questionnaire (AMQ) was employed to assess aggressive motivation. Results revealed that viewing a prosocial cartoon (versus a nonprosocial cartoon) did reduce children’s aggression immediately upon exposure. Specifically, males showed less aggressive behavior than females upon prosocial cartoon exposure, whilst males showed more aggressive behavior than females upon nonprosocial cartoon exposure. Mediational analysis suggested that the prosocial cartoon effect on aggression was partially mediated by aggressive motivation, especially for males. Consistent with Ggeneral Aggression Model (GAM), findings of the study indicated that short-term exposure to a prosocial cartoon decreased children’s aggression by reducing aggressive motivation.